Analisa Horizontal Handover Terhadap Qos Layanan Streaming Multimedia E-Learning Pada Jaringan WLAN 802.11 - Widyantara, I M.O.; Cahyono, Bagus D.; Setiawan, Widyadi (Jurnal Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i01p08)
In this globalization era, the state of the user who no longer occupies in a single place, but always moving, it is necessary to continuity of communication that will cause a handover. This paper intends to analyze the effect of 802.11 WLAN horizontal handover to the QoS of streaming e-learning. Methods of data collection process using the Cisco 3500 series access point that supports handover with existing network systems, ad-hoc network and type of hard handover. The results of the data analysis showed that the handover process is able to improve the QoS by gradually restored gradually, to get back to normal QoS
Keywords: Horizontal handover, WLAN 802.11, QoS, Multimedia Streaming, E-Learning